Thiopurine metabolite level and toxicity in Indians with inflammatory bowel disease. Issue 1 (September 2017) - Parkar, Suruchi P; Dherai, Alpa J; Desai, Devendra C; Ashavaid, Tester F
Abstract : In this study, we showed that thiopurine levels were in therapeutic range in only 28% of patients and suboptimal in the remaining patients. Based on metabolite levels, thiopurine dose was optimized in 26% of patients. In addition, it is for the first time that we have showed that Indian patients do not require lower doses as compared to Caucasians and they have in fact lower toxicity than that reported in literature. Abstract : Background and Aim: A lower dose requirement and higher toxicity of thiopurine is reported in Asian patients with inflammatory bowel disease (IBD) as compared with Caucasian patients. These reports are based on thiopurine methyltransferase measurement studies rather than metabolite estimation. We studied the utility of thiopurine metabolite estimation in Indian patients with IBD and compared dose and toxicity with Asian and Caucasian patients. Methods: In this prospective study, 6‐thioguanine nucleotide (6‐TGN) and 6‐methylmercaptopurine levels were determined by HPLC in 76 IBD patients treated with thiopurines. The levels were correlated with dose, disease activity, and toxicity. The dose‐related metabolite levels and toxicity were compared with Caucasian and Asian patients reported in literature. Results: Of the 76 patients (32 women, mean age: 35.9 [SD: 14.54] years, 36 Crohn's disease and 40 ulcerative colitis), 1 non‐compliant patient had undetectable level of metabolites. Of the 75 patients, 21(28%) had therapeutic level of 6‐TGN, 37(49%) had subtherapeutic level and 17(23%) had supratherapeutic level. The 6‐methylmercaptopurine levels ranged up to 4971 pmol/8 × 10 8 red blood cells. Six (8%) patients showed toxicity. Thiopurine dose was optimized in 20 (26.31%) patients. Dose‐based metabolite levels were comparable to Asian and Caucasian patients. The toxicity (8%) observed in our patients was less than that reported (12–39%). Conclusion: Half of the patients in this study had low and a quarter had high 6‐TGN levels. One‐fourth of the patients needed dose modification. The dose‐based metabolite levels were comparable and the toxicity was less than that reported in Asian and Caucasian patients.